Design of a thermally stable rGO-embedded remote phosphor for applications in white LEDs. Issue 2 (26th November 2014) - Song, Young-Hyun; Han, Gill Sang; Mang, Sung Ryul; Jung, Mong Kwon; Jung, Hyun Suk; Yoon, Dae-Ho
Abstract : An rGO-embedded remote phosphor was fabricated for white LED application. Abstract : An rGO-embedded remote phosphor was fabricated for white LED applications. Compared with the remote phosphor without rGO, the rGO-embedded one showed higher thermal quenching properties and is expected to be a promising candidate for a new remote phosphor and the realization of white LEDs.